BETA-ADRENOBLOCKERS IN XXI CENTURY: EPOCH END OR IMMORTALITY BEGINNING? A VIEW OF ORDINARY CARDIOLOGIST - L. N. Malaj (Рациональная фармакотерапия в кардиологии)
Usage of β-blockers (BB) for treatment of patients with cardiovascular diseases is discussed. Results of the basic clinical trials with BB (LIFE, ASCOT, etc.) are analyzed. The role of sympathetic system in different stages of cardiovascular continuum as well as forecast of BB clinical efficacy is surveyed. Author presents a review of data about selective β1-blocker, metoprolol succinate (Betalok ZОК), in patients with cardiovascular diseases.